Self-Reported Clinical Practice Skill Readiness of Final Year Nursing Students Studying in Bengaluru, Karnataka: An Institutional-Based Cross-Sectional Study - Upashe, Shivaleela P.; Shil, Rahul; Shetty, Shraddha (Journal of Health and Allied Sciences NU, 2022)
Introduction In recent few years, the production of nurses in both the public and private sectors has been growing rapidly to fill up the gap of health care staff. As there is a lack of data available on clinical practice readiness among final year nursing students in India, the question remains of how nursing students see themselves and what qualities and areas interest them are of great importance.Objectives This study was conducted to determine the clinical practice skill readiness among final year nursing students and also to explore the factors that show the significant difference with clinical practice skill readiness level.Methodology A nonexperimental institutional-based cross-sectional online survey was conducted from October 15 to November 15, 2020 using a simple random sampling technique. A total of 200 final year nursing students have participated in the study through the self-structured and prevalidated comprehensive nursing competencies questionnaire (CNCQ). Data was collected through Google Form and exported to SPSS version 20.0 for further analysis. To compare the nursing competencies score with selected demographic characteristics, a one-way analysis of variance and an unpaired t-test were applied at a 95% confidence interval (CI). The post hoc test was used to check for multiple comparisons.Results Results of the study revealed that the overall CNCQ mean score of basic nursing skills were reasonably high (39.08 ± 13.27) compared with advanced nursing care skills (13.03 ± 5.28). A significant difference (p < 0.05) was observed in overall clinical posting duration in both basic (p < 0.004) and advanced (p < 0.001) nursing skills with selected demographic variables. There is also a significant difference found in the overall level of qualification (p < 0.004) in basic nursing skills. It was observed that in basic nursing care skills half of the year clinical posting (minimum 6 months) duration had a significant difference with the improved performance skills (p < 0.005) (0.57; 95% CI 0.14–1.00). Whereas the results also show that, the advanced nursing skills will be greatly improved if the nursing students get an opportunity to practice in different specialty areas for at least 2 months (p < 0.013) (0.62; 95% CI 0.11–1.14) or half of the year (p < 0.001) (0.95; 95% CI 0.34–1.56). This result shows a clear indication of how important clinical posting for nursing students is.Conclusion Our data suggested that the final year nursing students are losing ground in clinical practice readiness and competency. The result also shows that the clinical competency score will greatly improve in both basic and advanced nursing skills if the students are exposed to the clinical areas at least for a few months. Our findings will support the stakeholders, authorities of nursing colleges, and policymakers to make a significant decision to enhance the clinical practice among final year nursing students.
Keywords: self-reported clinical practice; graduating nursing students; clinical performance